The Impact of Academic Stress on Student Mental Health: A Review of the Literature - Azeng Nurul Hikmah; Analekta Tiara Perdana (PT. Edukasi Ahmad Kirang, 2025)
Background: Academic stress is a prevalent issue among university students and has been widely associated with adverse mental health outcomes. Increasing academic demands, transitional challenges, and performance pressure place students at higher risk of experiencing psychological distress. Given the growing global concern regarding student mental health, this study aimed to examine the impact of academic stress on mental health among university students. This literature review sought to synthesize existing evidence and identify key trends related to academic stress and mental health outcomes. Methods: This study employed a narrative literature review design. Relevant articles published within the last ten years were identified through electronic databases using keywords related to academic stress, mental health, and university students. Studies were selected based on predefined inclusion criteria focusing on undergraduate and postgraduate students. Data were analyzed through critical reading and qualitative synthesis of findings from peer-reviewed journals. Ethical approval was not required as the study used secondary data. Results: The reviewed literature consistently demonstrated a strong association between academic stress and negative mental health outcomes. High levels of academic stress were linked to increased symptoms of anxiety, depression, emotional exhaustion, sleep disturbances, and reduced psychological well-being. Academic workload, examinations, time pressure, and insufficient academic support were identified as major stressors. Protective factors such as coping strategies, resilience, and social support were reported to reduce the negative effects of academic stress. Conclusion: This literature review highlights the significant impact of academic stress on university students’ mental health. The findings emphasize the need for promotive and preventive mental health strategies within higher education institutions. Future research should focus on intervention-based and longitudinal studies to strengthen mental health support systems for students